1999
DOI: 10.1046/j.1440-0960.1999.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery of benign skin lesions

Abstract: Cryosurgery is a widely used treatment modality in dermatology. Its place in cutaneous malignant and premalignant disease is well established; however, it also has great utility with benign lesions. Vascular, infectious, fibrotic diseases, solar damage, acne, as well as some cosmetic defects are amenable to freezing. The mechanism of treatment involves inducing tissue damage, vascular stasis and occlusion, as well as inflammation, to destroy unwanted tissue. After destruction of epidermal lesions, healing invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
15

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 38 publications
1
58
0
15
Order By: Relevance
“…Previous investigators have also found that color change due to cryotherapy was a transient side effect that resolves within months. 11,20,25,29 Although it is difficult to find a well-standardized scale for the assessment of scar quality in cases of CL, in general terms, scarring after cryotherapy was negligible in the majority (93.6%) of lesions. When noticeable, the scarring was not exaggerated and not beyond that which may occur after self-healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have also found that color change due to cryotherapy was a transient side effect that resolves within months. 11,20,25,29 Although it is difficult to find a well-standardized scale for the assessment of scar quality in cases of CL, in general terms, scarring after cryotherapy was negligible in the majority (93.6%) of lesions. When noticeable, the scarring was not exaggerated and not beyond that which may occur after self-healing.…”
Section: Discussionmentioning
confidence: 99%
“…19,21,23 This finding suggests that short-interval sessions may have the potential to minimize the possibility of proliferation and reestablishment of the surviving parasites in the lesion. The effect of cryotherapy on host tissues involves the triggering of immune mechanisms and vascular stasis in the lesion, 24,25 which, in addition to other changes, can affect the healing process.…”
mentioning
confidence: 99%
“…Thermosensitive Leishmania are killed by the subzero temperature induced by cryotherapy, 36,45 which also triggers a host immune response and vascular stasis of the lesion. 46,47 The therapeutic value of cryotherapy has been established but with varying efficacy. 5,32,48 One study by Panagiotopoulos et al 49 reported that all patients responded well to therapy with excellent cosmetic results and no relapse.…”
Section: Leishmaniasismentioning
confidence: 99%
“…Recently techniques such as dermabrasion and cryosurgery have shown limited success. In recent years lasers and white light systems have demonstrated significant therapeutic benefit without side effects (15,16).…”
Section: Benign Pigmented Lesionsmentioning
confidence: 99%